Trifluoromethyl ethers – synthesis and properties of an unusual substituent - Leroux, Frédéric R.; Manteau, Baptiste; Vors, Jean-Pierre; Pazenok, Sergiy (Beilstein Journal of Organic Chemistry, 2008)
After nitrogen, fluorine is probably the next most favorite hetero-atom for incorporation into small molecules in life science-oriented research. This review focuses on a particular fluorinated substituent, the trifluoromethoxy group, which is finding increased utility as a substituent in bioactives, but it is still perhaps the least well understood fluorine substituent in currency. The present review will give an overview of the synthesis, properties and reactivity of this important substituent.

(untitled) - Thayer, A. M. (Chem. Eng. News, 2006)

The Pesticide Manual - Tomlin, C. D. S. (British Crop Protection Council, 2003)

Chemistry of Organic Fluorine Compounds II: A Critical Review - Elliott, A. J. (American Chemical Society, 1995)

Organofluorine Chemistry: Principles and Commercial Applications - Edwards, P. N. (Uses of Fluorine in Chemotherapy, 1994)

Organofluorine Compounds in Medicinal Chemistry and Biomedical Applications - Filler, R.; Kobayashi, Y.; Yagupolskii, L. M. (Elsevier, 1993)

Biomedicinal Aspects of Fluorine Chemistry - Filler, R.; Kobayashi, Y. (Kodansha Ltd., 1982)

Biomedical Frontiers of Fluorine Chemistry - Ojima, I.; McCarthy, J. R.; Welch, J. T. (American Chemical Society, 1996)

Fluorine in Bioorganic Chemistry - Welch, J. T.; Eswarakrishnan, S. (Wiley, 1991)

Organofluorine Chemistry: Principles and Commercial Applications - Banks, R. E.; Smart, B. E.; Tatlow, J. C. (Plenum Press, 1994)

(untitled) - Jeschke, P.; Baston, E.; Leroux, F. R. (Mini-Rev. Med. Chem., 2007)

(untitled) - Jeschke, P. (ChemBioChem, 2004)

(untitled) - Leroux, F.; Jeschke, P.; Schlosser, M. (Chem. Rev., 2005)

(untitled) - Larsen, E. R. (Fluorine Chem. Rev., 1969)

(untitled) - Bagnall, R. D.; Bell, W.; Pearson, K. (J. Fluorine Chem., 1977)

(untitled) - Franks, N. P.; Lieb, W. R. (Nature, 1994)

(untitled) - Yagupol'skii, L. M. (Dokl. Akad. Nauk SSSR, 1955)

(untitled) - Yarovenko, N. N.; Vasil'eva, A. S. (Zh. Obshch. Khim., 1958)

(untitled) - Yagupol'skii, L. M.; Orda, V. V. (Zh. Obshch. Khim., 1964)

(untitled) - Yagupol'skii, L. M.; Troitskaya, V. I. (Zh. Obshch. Khim., 1961)

(untitled) - Louw, R.; Franken, P. W. (Chem. Ind., 1977)

(untitled) - Feiring, A. E. (J. Org. Chem., 1979)

(untitled) - Mathey, F.; Bensoam, J. (Tetrahedron Lett., 1973)

(untitled) - Sheppard, W. A. (J. Org. Chem., 1964)

(untitled) - Kanie, K.; Tanaka, Y.; Suzuki, K.; Kuroboshi, M.; Hiyama, T. (Bull. Chem. Soc. Jpn., 2000)

(untitled) - Kuroboshi, M.; Kanie, K.; Hiyama, T. (Adv. Synth. Catal., 2001)

(untitled) - Kuroboshi, M.; Suzuki, K.; Hiyama, T. (Tetrahedron Lett., 1992)

(untitled) - Shimizu, M.; Hiyama, T. (Angew. Chem., Int. Ed., 2005)

(untitled) - Umemoto, T.; Adachi, K.; Ishihara, S. (J. Org. Chem., 2007)

(untitled) - Umemoto, T.; Ishihara, S. (Tetrahedron Lett., 1990)

(untitled) - Umemoto, T.; Ishihara, S. (J. Am. Chem. Soc., 1993)

(untitled) - Umemoto, T.; Adachi, K. (J. Org. Chem., 1994)

(untitled) - Yagupol'skii, L. M.; Kondratenko, N. V.; Timofeeva, G. N. (Zh. Org. Khim., 1984)

(untitled) - Kieltsch, I.; Eisenberger, P.; Togni, A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Eisenberger, P.; Gischig, S.; Togni, A. (Chem.–Eur. J., 2006)

(untitled) - Aldrich, P. E.; Sheppard, W. A. (J. Org. Chem., 1964)

(untitled) - Umemoto, T. (Chem. Rev., 1996)

(untitled) - Rozen, S. (Chem. Rev., 1996)

(untitled) - Trainor, G. L. (J. Carbohydr. Chem., 1985)

(untitled) - Farnham, W. B.; Smart, B. E.; Middleton, W. J.; Calabrese, J. C.; Dixon, D. A. (J. Am. Chem. Soc., 1985)

(untitled) - Ben-David, I.; Rechavi, D.; Mishani, E.; Rozen, S. (J. Fluorine Chem., 1999)

(untitled) - Yagupol'skii, L. M.; Alekseenko, A. N.; Il'chenko, A. Y. (Ukr. Khim. Zh. (Russ. Ed.), 1978)

(untitled) - Kollonitsch, J.; Marburg, S.; Perkins, L. M. (J. Org. Chem., 1976)

(untitled) - Sondej, S. C.; Katzenellenbogen, J. A. (J. Org. Chem., 1986)

(untitled) - Blazejewski, J.-C.; Anselmi, E.; Wakselman, C. (J. Org. Chem., 2001)

(untitled) - Kimura, K.; Kubo, M. (J. Chem. Phys., 1959)

(untitled) - Praly, J.-P.; Brard, L.; Descotes, G.; Toupet, L. (Tetrahedron, 1989)

(untitled) - Oberhammer, H. (J. Fluorine Chem., 1983)

(untitled) - McClinton, M. A.; McClinton, D. A. (Tetrahedron, 1992)

(untitled) - Böhm, H.-J.; Banner, D.; Bendels, S.; Kansy, M.; Kuhn, B.; Müller, K.; Obst-Sander, U.; Stahl, M. (ChemBioChem, 2004)

(untitled) - Olah, G. A.; Yamato, T.; Hashimoto, T.; Shih, J. G.; Trivedi, N.; Singh, B. P.; Piteau, M.; Olah, J. A. (J. Am. Chem. Soc., 1987)

(untitled) - Sheppard, W. A. (J. Am. Chem. Soc., 1963)

(untitled) - Haas, A. (Adv. Inorg. Chem. Radiochem., 1984)

Substituent Constants for Correlation Analysis in Chemistry and Biology - Hansch, C.; Leo, A. (John Wiley and Sons, 1979)

(untitled) - Leo, A.; Jow, P. Y. C.; Silipo, C.; Hansch, C. (J. Med. Chem., 1975)

(untitled) - Yagupol'skii, L. M.; Yagupol'skaya, L. N. (Dokl. Akad. Nauk SSSR, 1960)

(untitled) - Yagupol'skii, L. M.; Bystrov, V. F.; Stepanyants, A. U.; Fialkov, Y. A. (Zh. Obshch. Khim., 1964)

(untitled) - Sheppard, W. A. (J. Am. Chem. Soc., 1962)

Dissociation Constants of Organic Acids in Aqueous Solution - Kortüm, G.; Vogel, W.; Andrussow, K. (Butterworths & Co., 1961)

(untitled) - Kortüm, G.; Vogel, W.; Andrussow, K. (Pure Appl. Chem., 1961)

(untitled) - Hansch, C.; Leo, A.; Taft, R. W. (Chem. Rev., 1991)

(untitled) - Ansink, H. R. W.; Cerfontain, H. (Recl. Trav. Chim. Pays-Bas, 1992)

(untitled) - Desbois, M. (Bull. Soc. Chim. Fr., 1986)

(untitled) - Bunton, C. A.; Minkoff, G. J.; Reed, R. I. (J. Chem. Soc., 1947)

(untitled) - Shelyazhenko, S. V.; Fialkov, Y. A.; Yagupol'skii, L. M. (Zh. Org. Khim., 1992)

(untitled) - Meldola, R.; Woolcott, G. H.; Wray, E. (J. Chem. Soc., Trans., 1896)

The Chemistry of Organolithium Compounds - Leroux, F.; Schlosser, M.; Zohar, E.; Marek, I. (The Preparation of Organolithium Reagents and Intermediates, 2004)

(untitled) - Schlosser, M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Leroux, F.; Castagnetti, E.; Schlosser, M. (J. Org. Chem., 2003)

(untitled) - Castagnetti, E.; Schlosser, M. (Eur. J. Org. Chem., 2001)

German Patent DE - Pauluth, D.; Haas, H. ((Merck Patent GmbH, Darmstadt, Germany) Verfahren zur Herstellung von substituiertem Trifluormethoxybenzol, 1993)

(untitled) - Schlosser, M.; Castagnetti, E. (Eur. J. Org. Chem., 2001)

(untitled) - Castagnetti, E.; Schlosser, M. (Chem.–Eur. J., 2002)